Edukasi Anti Kekerasan Seksual dan Perundungan (Bullying) pada Siswa SMK X Kota Batam - Herdianti, Herdianti; Martha, Elsusi; Kafit, M.; Sembiring, Firdaus Yustisi; Arnanda, Riyansyah (ASOSIASI IDEBAHASA KEPRI, 2024)
Prevention of sexual violence is an important program that every school must have. The ideal prevention program is a program that is initiated from below, namely from the hopes of all students, teachers and all stakeholders. Bullying is a loan word from English. Bullying comes from the word bully which means bully, someone who bullies weak people. Based on the proliferation of bullying cases in educational institutions in Indonesia, especially in the school environment, the author determines the location for outreach related to bullying behavior at the educational level. The service activity aims to develop a school-based sexual violence and bullying prevention program with stages focus group discussion (FGD) and campaigns to prevent sexual violence and bullying. This activity was held on Wednesday, February 14 2024, and will be attended by students from X High School, Batam City. The aim of this activity is to provide a preventive impact on students so that sexual violence and bullying behavior does not occur in the school, family or community environment. The results of the FGD show that most students have sufficient knowledge about sexual violence. They associate sexual violence with sexual activity, while non-sexual behavior is considered unrelated to sexual violence. Many students have been victims or witnesses of sexual violence at school, home and public places. Students recommended that sexual assault prevention programs focus on students' needs and perspectives. The next step is to develop a school-based sexual violence prevention program based on student input.